PS-C10-8: ANALYSIS OF OFFICE SYSTOLIC BLOOD PRESSURE MEASURED BY VARIOUS METHODS IN DIFFERENT CONDITIONS. (January 2023) - Muzik, Jan; Peleska, Jan; Holubova, Anna; Camek, Rene; Navratil, Vojtech; Fiala, Dominik; Doksansky, Marek; Hana, Karel; Kaspar, Jan; Vranka, Jakub; Hronova, Julie; Chrolenko, Anna; et al.
Abstract : Objectives: The aim of the study is to confirm results of our pilot study (presented ESH/ISH Glasgow 2021) and perform a detailed analysis of the larger sample size. Design and Method: BP monitors Nissei DM-3000 (both auscultatory and oscillometric), SunTech-40 and Fora P30 Plus, in both conditions, were used for office BP measurements (BPM) in triplets by one physician at the entry and exit phase of the 3 months home BP telemonitoring study. 122 treated patients with essential hypertension, aged 24–85 years, 60% of males, were referred by their physicians as well controlled. Their therapy was not changed during this study. Those starting BPMs in the office at the entry, started BPMs in the quiet room at the exit, and vice versa, approximately at the same time. On the other hand, the order of methods used both in the office and in the quiet room was not changed. Effects of gender, age, BMI, order of BPM (physician/quiet room - P/QR, order of BPM in triplets) and methods of BPM on systolic BP at the entry and exit of the study were evaluated. Linear mixed models with random effect of a patient were used for the statistical analysis of data. Results: Systolic BP (SBP) values significantly depended on the morning medication (yes, no, p = 0.005) and the method of BPM used (p < 0.001). SBP values of various methods varied in dependence on the phase of the study (entry, exit, p < 0.001), age (< 60, > = 60, p < 0.001) and BMI (< 30, > = 30, p < 0.001). SBP was not dependent on the measurement order P/QR significantly. If each method of BPM was analyzed independently on other ones, only auscultatory SBP depended significantly on the measurement order in triplets (p < 0.001). Decrease of mean SBP+SD from the first to the third BPM was seen only at the entry phase of the study - 128.8 + 13.0, 126.0 + 13.5 and 124.7 + 12.6 mmHg. Conclusions: Significant differences between BPM methods used in systolic BP measurement were found. Fora BP monitor showed especially higher mean SBP values probably due to a stress from the first contact with a telemonitoring equipment in the quiet room only at the entry (132.0 + 12.9) vs. (127.3 + 12.3) mmHg. We did not prove any influence of measurement order P/QR even when Fora was used in both attended and unattended conditions. If an independent analysis of BPM methods was used, only auscultatory SBP depended significantly on the measurement order in triplets, whereas no significant influence was shown in oscillometric methods.